Antiparasitic and Antifungal Activities of Cetyl-Maritima, a New N-Cetyl-Modified Maritima Derivative - Ibrahim S. Al Nasr; Jingyi Ma; Tariq A. Khan; Waleed S. Koko; Imen Ben Abdelmalek; Rainer Schobert; Wendy van de Sande; Bernhard Biersack (Antibiotics)
Background/Objectives: New drugs are urgently needed for the treatment of neglected tropical diseases including leishmaniasis and eumycetoma, as well as globally occurring parasitic diseases such as toxoplasmosis. Fragrances, both natural and synthetic, were shown to be a rich source for the development of new anti-infectives and warrant deeper investigations. Exemplarily, we synthetically optimized the fragrance 4-(4,8-dimethyl-3,7-nonadienyl)-pyridine, a.k.a. Maritima, a pyridine derivative with marine odor. Methods: A new cationic N-cetyl-modified derivative of Maritima (dubbed Cetyl-Maritima), obtained by alkylation of Maritima, was tested for its activity against Madurella mycetomatis (M. mycetomatis) fungi, as well as against Toxoplasma gondii (T. gondii) and Leishmania major (L. major) protozoal parasites. Results: Cetyl-Maritima was found to be more strongly antifungal than the parent Maritima and a known antibiotic cetylpyridinium salt. Cetyl-Maritima also showed a similar activity against T. gondii parasites and, most notably, exhibited sub-micromolar activity against L. major amastigotes. Conclusions: The considerable antileishmanial activity of Cetyl-Maritima might lead to the development of a new potent and cost-effective drug candidate for the therapy of leishmaniasis and other infectious diseases caused by kinetoplastid parasites.